Integrated Indoor and Outdoor Topological Modeling - W. Zhao; W. Zhao; W. Zhao; Z. Kang; Z. Kang; Z. Kang; C. Ye; C. Ye; C. Ye (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2025)
With the rapid advancement of urbanization, the spatial structures of large-scale public venues such as transportation hubs and shopping malls have become increasingly complex. These venues often include diverse and flexible types of transitional spaces connecting them with their surrounding environments, which impose a significant cognitive burden on individuals navigating through them. However, traditional methods for constructing indoor and outdoor geospatial data for location-based services (LBS) are typically conducted independently. These approaches lack a unified topological characterization of transitional spaces, leading to several challenges in practical applications, such as the disconnection between indoor and outdoor spaces, difficulties in cross-scene transitions, and inaccurate topological correspondences between indoor and outdoor spaces. This highlights the critical need for an integrated indoor-outdoor topological modeling approach. To address these issues, this study proposes a systematic workflow for constructing an integrated indoor-outdoor topological model based on complete transitional spaces derived from indoor and outdoor point cloud data. This approach provides foundational support for subsequent applications, such as path navigation and emergency planning for unmanned aerial vehicles (UAVs).